Advanced university physics - Palmer, Stuart B; Rogalski, Mircea S. (Chapman & Hall/CRC, 2006)
Presents a condensed sequence of physical principles that link macroscopic mechanical, thermal, and electrical phenomena to their microscopic quantum origin, statistical description, and atomic structure. This book uses simple models and allows contact with the behavior of real phenomena, real substances, and aspects of research.